Hybrid micro/nano-topography of a TiO(2) nanotube-coated commercial zirconia femoral knee implant promotes bone cell adhesion in vitro - Frandsen, Christine J. (2013)
Various approaches have been studied to engineer the implant surface to enhance bone in-growth properties, particularly using micro- and nano- topography. In this study, the behavior of osteoblast (bone) cells was analyzed in response to a titanium oxide (TiO(2)) nanotube-coated commercial zirconia femoral knee implant consisting of a combined surface structure of a micro-roughened surface with the nanotube coating. The osteoblast cells demonstrated high degrees of adhesion and integration into the surface of the nanotube-coated implant material, indicating preferential cell behavior on this surface when compared to the bare implant. The results of this brief study provide sufficient evidence to encourage future studies. The development of such hierarchical micro and nano topographical features, as demonstrated in this work, can provide for insightful designs for advanced bone-inducing material coatings on ceramic orthopedic implant surfaces.